Inevitable Results and Political Myths? Ilford North's 1978 By‐Election*. (1st June 2022) - Collinson, Marc
Abstract: Reductive and teleological 'path to power' myths continue to underpin explanations of Margaret Thatcher's first general election success. The by‐elections that eroded the Callaghan government's majority in the late 1970s, such as that at Ilford North in 1978, continue to be discussed as stepping stones to an inevitable victory, rather than acknowledged as examples of the fraught and uncertain realities of electoral politics. This article argues that they should be considered as part of a complicated historical process and reflected concurrent socio‐economic, cultural and political change. Such contests deserve to be understood on their own terms, with awareness of their unique peculiarities. In full media glare and an often carnival atmosphere, small, often ignored, constituencies momentarily captured the political zeitgeist and determined the national debate. Consequently, earlier interpretations of the contest that advocated the importance of media‐induced concerns over immigration and the National Front have distracted from the effectiveness of Conservative strategy that delivered a successful homecoming, rather than an overwhelming shock victory. By moving beyond contemporary political myths, it reconsiders the strength of Britain's political parties within a more historical context, which pointed to the depth of local Conservative support in Ilford North. Clear political strategy including well‐articulated appeals to specific voter groups and a well‐managed media maelstrom, allowed Margaret Thatcher's party to re‐establish its support among Ilford North's voters.